Pengembangan Soal Open-Ended Pokok Bahasan Barisan dan Deret Bilangan untuk Siswa SMP - Yusliriadi Yusliriadi; Darmawijoyo Darmawijoyo; Somakim Somakim (Universitas Hamzanwadi, 2015)
The research is proposed to: (1) get open-ended problems which are valid and practice on the math topic Sequence and Series of numbers for junior high school students. (2) find potential effects of open ended problems to the students on the topic about sequence and series of numbers. The methodology that use in this study is a developmental research. The way of collecting data is by using Walk through, to determine the validity of the matter is the content, construct, and language; document at small group to know about the practicality; tests and interviews to find out about the potential effects on the ability of students' understanding of the concept. The result of data analysis come to conclusion, that: (1) This research produces (six question) open ended problems on the topic of sequence and series of numbers for students of IX grade are valid and practice. (2) The prototype of open-ended problems which was developed have positive potential effect to the ability of students’ understanding of the concept, it is shown by the average value of students’ understanding of the concept of good in the open-ended problems test which resulted 71,9%.